Transforming Growth Factor-Beta and Sonic Hedgehog Signaling in Palatal Epithelium Regulate Tenascin-C Expression in Palatal Mesenchyme During Soft Palate Development - Ohki, Shirabe; Oka, Kyoko; Ogata, Kayoko; Okuhara, Shigeru; Rikitake, Mihoko; Toda-Nakamura, Masako; Tamura, Shougo; Ozaki, Masao; Iseki, Sachiko; Sakai, Takayoshi (Frontiers in Physiology, 2020)
During palatogenesis, the palatal shelves first grow vertically on either side of the tongue before changing their direction of growth to horizontal. The extracellular matrix plays an important role in these dynamic changes in palatal shelf morphology. Tenascin-C (TNC) is an extracellular matrix glycoprotein that shows unique expression in the posterior part of the palatal shelf, but little is known about the regulation of TNC expression. Since transforming growth factor-beta-3 (TGF-b3) and sonic hedgehog (SHH) signaling are known to play important roles in palatogenesis, we investigated whether TGF-b3 and SHH are involved in the regulation of TNC expression in the developing palate. TGF-b3 increased the expression of TNC mRNA and protein in primary mouse embryonic palatal mesenchymal cells (MEPM) obtained from palatal mesenchyme dissected at embryonic day 13.5-14.0. Interestingly, immunohistochemistry experiments revealed that TNC expression was diminished in K14-cre;Tgfbr2fl/fl mice and exhibit cleft soft palate, whereas TNC expression was maintained in Wnt1-cre;Tgfbr2fl/fl mice and exhibit a complete cleft palate. SHH also increased the expression of TNC mRNA and protein in MEPM cells. However, although TGF-b3 up-regulated TNC mRNA and protein expression in O9-1 cells (a cranial neural crest cell line), SHH did not. Furthermore, TGF-b inhibited the expression of osteoblastic differentiation markers (osterix and alkaline phosphatase) and induced the expression of fibroblastic markers (fibronectin and periostin) in O9-1 cells, whereas SHH did not affect the expression of osteoblastic and fibroblastic markers in O9-1 cells. However, immunohistochemistry experiments showed that TNC expression was diminished in the posterior palatal shelves of Shh−/+;MFCS4+/− mice, which have deficient SHH signaling in the posterior palatal epithelium. Taken together, our findings support the proposal that TGF-b and SHH signaling in palatal epithelium co-ordinate the expression of TNC in the posterior palatal mesenchyme through a paracrine mechanism. This signal cascade may work in the later stage of palatogenesis when cranial neural crest cells have differentiated into fibroblast-like cells. The spatiotemporal regulation of extracellular matrix-related proteins by TGF-b and SHH signaling may contribute not only to tissue construction but also to cell differentiation or determination along the anterior-posterior axis of the palatal shelves.